1989
DOI: 10.1161/01.cir.80.4.863
|View full text |Cite
|
Sign up to set email alerts
|

Regional myocardial oxygen consumption determined noninvasively in humans with [1-11C]acetate and dynamic positron tomography.

Abstract: Experimental studies of animals have previously demonstrated the validity of [1-ttClacetate as a tracer of oxidative metabolism for use with positron emission tomography. The present study was undertaken to define in normal human volunteers the relation between myocardial clearance kinetics of [1-"C]acetate, and the rate-pressure product as an index of myocardial oxygen consumption. Twenty-two studies were performed of 12 volunteers. The rate-pressure product was increased with continuous supine bicycle exerci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
53
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(56 citation statements)
references
References 35 publications
2
53
1
Order By: Relevance
“…An understanding of the quantitative extent of these alterations is important for both diagnosis and therapy in reperfused myocardium. For example, clearance of "C-enriched acetate may be monitored in patients by positron tomography (7)(8)(9), yet the biochemical basis of altered tracer clearance during ischemia is incompletely understood (10)(11)(12). Of perhaps greater significance is the potential for improving recovery after ischemia by deliberately modifying carbon flow into the citric acid cycle.…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of the quantitative extent of these alterations is important for both diagnosis and therapy in reperfused myocardium. For example, clearance of "C-enriched acetate may be monitored in patients by positron tomography (7)(8)(9), yet the biochemical basis of altered tracer clearance during ischemia is incompletely understood (10)(11)(12). Of perhaps greater significance is the potential for improving recovery after ischemia by deliberately modifying carbon flow into the citric acid cycle.…”
Section: Introductionmentioning
confidence: 99%
“…However, direct measurement of aerobic metabolic flux in small myocardial regions became possible only recently. Regional V O 2 and regional blood flow can be estimated with PET, although this technique still does not permit analysis at sufficiently high spatial resolution to study cardiac heterogeneity in small tissue areas (1,34,37).To investigate the distribution of MV O 2 at high spatial resolution, a new combination of isotope labeling protocol and mathematical analysis of 13 C incorporation into the tricarboxylic acid (TCA) cycle has been developed by us (43). …”
mentioning
confidence: 99%
“…In such cases, 11 C-acetate clearance may severely overestimate adenosine triphosphate resynthesis and underestimate MVO 2 . On the other hand, earlier studies with healthy volunteers and experimental canine studies showed that changes in the availability of myocardial metabolic substrates or ischemia, without changes in hemodynamics, did not affect LV 11 C-acetate kinetics, with similar relationships between K mono and either MVO 2 or RPP at normal baseline conditions (23)(24)(25).…”
Section: Discussionmentioning
confidence: 89%
“…In the present study, test-retest variability was not investigated, as adding a scan was not feasible for the present patient population. The reproducibility of 11 C-acetate clearance rate measurements in humans has been demonstrated by Armbrecht et al (24). The fact that the measurement of pulmonary artery pressure and heart rate for the calculation of RPP was performed on another day may also have contributed to error variance.…”
Section: Discussionmentioning
confidence: 90%